2019
DOI: 10.1038/s41598-019-49303-w
|View full text |Cite
|
Sign up to set email alerts
|

Tuning of the Electro-Optical Properties of Tetraphenylcyclopentadienone via Substitution of Oxygen with Sterically-Hindered Electron Withdrawing Groups

Abstract: In this report, the substitution of the oxygen group (=O) of Tetraphenylcyclopentadienone with =CR 2 group (R = methyl ester or nitrile) was found to have tuned the electro-optical properties of the molecule. Although both groups are electrons withdrawing in nature, their absorption from UV-vis spectra analysis was observed to have been blue-shifted by methyl ester substitution and red-shifted by nitrile substitution. Interestingly, these substitutions helped to enhance the overall inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 70 publications
1
9
0
Order By: Relevance
“…The electron-withdrawing groups do not have such a stabilization effect on the positive charge of the nitrogen atom and therefore do not change the energy gap. It is usual to see such shifts in the positions of absorption maxima, depending on the identity of the substitution. , Very similar effects were observed by Enchev et al They reported that although replacing the hydrogen with a chlorine was shifting the absorption maxima of their parent azacyanine by only 9 nm, replacing it with a methoxy group was shifting it about 30 nm. On the other hand, broadness of the absorption peaks is due to the presence of several vibrational and rotational states corresponding to the ground state and the excited states. , The presence and the identity of the substitution of the ring system might be one of the possible reasons behind the observed differences in broadness.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…The electron-withdrawing groups do not have such a stabilization effect on the positive charge of the nitrogen atom and therefore do not change the energy gap. It is usual to see such shifts in the positions of absorption maxima, depending on the identity of the substitution. , Very similar effects were observed by Enchev et al They reported that although replacing the hydrogen with a chlorine was shifting the absorption maxima of their parent azacyanine by only 9 nm, replacing it with a methoxy group was shifting it about 30 nm. On the other hand, broadness of the absorption peaks is due to the presence of several vibrational and rotational states corresponding to the ground state and the excited states. , The presence and the identity of the substitution of the ring system might be one of the possible reasons behind the observed differences in broadness.…”
Section: Resultssupporting
confidence: 59%
“…It is usual to see such shifts in the positions of absorption maxima, depending on the identity of the substitution. 34 , 35 Very similar effects were observed by Enchev et al 18 They reported that although replacing the hydrogen with a chlorine was shifting the absorption maxima of their parent azacyanine by only 9 nm, replacing it with a methoxy group was shifting it about 30 nm. On the other hand, broadness of the absorption peaks is due to the presence of several vibrational and rotational states corresponding to the ground state and the excited states.…”
Section: Resultsmentioning
confidence: 53%
“…Consequently, we selected trichlorotriazine (TCT) to carry out nucleophilic substitution reactions with 2,3,4,5-tetraphenylcyclopenta-2,4-dien-1-one (CP) and 2-(2,3,4,5-tetraphenylcyclopenta-2,4-dien-1-ylidene) malononitrile (CPM) to obtain triazine-based CP-TCT and CPM-TCT CMPs, respectively (Scheme 1). Precursors CP and CPM were synthesized in good yields following literature procedures 70,71 as presented in the synthetic routes in Schemes S1 and S2 and The CMPs containing the triazine moiety were constructed using the metal-free Friedel-Crafts simple polymerization reaction of TCT with both CP and CPM, in o-dichlorobenzene at 140 °C, using a methane-sulfonic acid catalyst, as illustrated in Schemes 1, S3, and S4 †. The reaction yields of the prepared polymers CP-TCT and CPM-TCT CMPs were 67.3% and 53.5%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, we selected trichlorotriazine (TCT) to carry out nucleophilic substitution reactions with 2,3,4,5-tetraphenylcyclopenta-2,4-dien-1-one (CP) and 2-(2,3,4,5-tetraphenylcyclopenta-2,4-dien-1-ylidene) malononitrile (CPM) to obtain triazine-based CP-TCT and CPM-TCT CMPs, respectively (Scheme 1). Precursors CP and CPM were synthesized in good yields following literature procedures 70,71 as presented in the synthetic routes in Schemes S1 and S2 and Fig. S1–S6†.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation